2019
DOI: 10.1002/ptr.6326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of turmeric and curcumin on oral mucositis: A systematic review

Abstract: The aim of this study was to evaluate the effects of turmeric and curcumin in the management of oral mucositis in cancer patients undergoing chemo and/or radiotherapy. The systematic review was reported according to the Preferred Reporting Items for Systematic reviews and Meta‐Analyses. The search was performed in the following database: Cochrane Library, LILACS, LIVIVO, PubMed, Scopus, and Web of Science. A gray literature search was undertaken using Google Scholar, Open Grey, and ProQuest. The methodology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 37 publications
2
26
0
2
Order By: Relevance
“…The severity of oral mucositis was found to significantly decrease in the treatment group compared to the control group. This finding has also been confirmed in other studies that examined the efficacy of free curcumin for this purpose (Normando et al., 2019). Nanocurcumin, therefore, has the potential to be a reasonable agent to hinder the development of oral mucositis in patients with head and neck cancer who require radiotherapy.…”
Section: Resultssupporting
confidence: 81%
“…The severity of oral mucositis was found to significantly decrease in the treatment group compared to the control group. This finding has also been confirmed in other studies that examined the efficacy of free curcumin for this purpose (Normando et al., 2019). Nanocurcumin, therefore, has the potential to be a reasonable agent to hinder the development of oral mucositis in patients with head and neck cancer who require radiotherapy.…”
Section: Resultssupporting
confidence: 81%
“…It is tempting to hypothesize that this effect may be mediated by Glucosamine present in Ocoxin, since its supplementation leads to downregulation of nuclear factor kappa-light-chainenhancer of activated B cells (NF-κβ), which in turn decreased inflammatory mediators such as IL-1β and TNF-α [56]. On the other hand, antioxidant potential of Ocoxin may block the synthesis of ROS and NOS during mucositis, in concordance with other findings reporting improved oral pathology using natural compounds with antioxidant and anti-inflammatory properties [57,58].…”
Section: Ocoxin Improves Ct and Rt Related Toxicitysupporting
confidence: 71%
“…Curcumin is a natural polyphenol isolated from Curcuma longa that has been extensively studied in the past years, mostly because of its antioxidant, antimicrobial, and antiinflammatory properties (Edwards et al, 2017; Kahkhaie et al, 2019; Kotha & Luthria, 2019). Such effects might be explained by its ability to interact with different transcription factors, inflammatory mediators, and protein kinases, and therefore modulate signaling pathways that are linked to several disorders (Kahkhaie et al, 2019; Kunnumakkara et al, 2017; Normando et al, 2019). A recent overview identified 22 systematic reviews that reported the clinical efficacy of curcumin‐containing nutraceuticals in metabolic and inflammatory‐related diseases; however, due to the poor quality of the primary trials and the low‐to‐moderate level of reviews, there is still some uncertainty (Izzo, 2020; Pagano, Romano, Izzo, & Borrelli, 2018).…”
Section: Introductionmentioning
confidence: 99%